The Formation of Creative Thinking of Students's Higher Education System in the form - Kumush Narziyeva Qaxramonovna (Peerian Journals Publishing, 2022)
In order to increase the creativity of students of higher educational institutions, this article describes the exemplary parts of increasing creativity, thinking fluency, thinking flexibility, technology for developing creative thinking, increasing creativity based on SMART technology, technology for developing creativity with examples.
Keywords: creative thinking; brainstorming; digital technologies; flexibility